2015
DOI: 10.1002/adsc.201500453
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) Complexes Bearing Carbenes Beyond Classical N‐Heterocyclic Carbenes: Synthesis and Catalytic Activity in “Click Chemistry”

Abstract: Thes ynthesis andc haracterization of abnormal N-heterocyclic carbene,c yclic (alkyl)(amino)carbene,a nd mesoionic carbene copper(I) complexesa re reported.T hese organometallic species are obtained via aversatile and inexpensive synthetic pathwayu sing readily available reactants,n amely copper oxide andi miniums alts.T he catalytic activity of this series of complexes was evaluated in the [3+ +2] cycloaddition of alkynes with azides (CuAAC). Outstanding catalytic properties were observed for the abnormal NHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 83 publications
2
77
0
1
Order By: Relevance
“…Under the same conditions no conversion of 15 a was observed within two days.However, in the presence of 2equiv of CuCl, complex 12 a was formed within 30 minutes. [28] This results strongly support the classical mechanism in which active,14-electron species are formed via neutral ligand release and also prove that for 15 a dissociation of CAAC is the rate-limiting step.NMR kinetic studies were undertaken to gain more information about the possible mechanism of initiation of 15 f.T he rate of the reaction between 15 f and olefin 13 ([D 8 ]toluene,6 08 8C) proved to be independent of the concentration of 13 (see the Supporting Information) and was in good agreement with the stability of 15 f in solution (which appears to be limited by the high lability and low stability of CAAC). [25] Experimental results suggest that ad issociative mechanism operates for 15 f (Scheme 3).…”
Section: Angewandte Chemiesupporting
confidence: 80%
See 1 more Smart Citation
“…Under the same conditions no conversion of 15 a was observed within two days.However, in the presence of 2equiv of CuCl, complex 12 a was formed within 30 minutes. [28] This results strongly support the classical mechanism in which active,14-electron species are formed via neutral ligand release and also prove that for 15 a dissociation of CAAC is the rate-limiting step.NMR kinetic studies were undertaken to gain more information about the possible mechanism of initiation of 15 f.T he rate of the reaction between 15 f and olefin 13 ([D 8 ]toluene,6 08 8C) proved to be independent of the concentration of 13 (see the Supporting Information) and was in good agreement with the stability of 15 f in solution (which appears to be limited by the high lability and low stability of CAAC). [25] Experimental results suggest that ad issociative mechanism operates for 15 f (Scheme 3).…”
Section: Angewandte Chemiesupporting
confidence: 80%
“…[36] Moreover,avery high selectivity of 98 %w as observed without any additive typically applied to inhibit the C=Cbond migration. Under the same conditions,2 ppm of catalyst 1 delivered dimer 27 with only 31 %yield and 95 %selectivity 28 of 170 000. Self-metathesis of methyl oleate 7 proceeded up to 45 %ofconversion in the presence of 5ppm of 15 f.Almost quantitative yield in challenging cross-metathesis of ester 9 with electron-deficient methyl acrylate 29 was achieved with 200 ppm of 15 f.A dditionally,a lkene-alkyne (ene-yne) RCM of 31 and ROMP of norbornene 33 were successfully accomplished with the use of 250 and 1000 ppm of 15 f,r espectively.T he obtained polynorbornene 34 was characterized by an umber-average molecular weight of 61 kg mol À1 ,w eight-average molecular weight of 110 kg mol À1 ,and polydispersity (PDI) of 1.81.…”
Section: Angewandte Chemiementioning
confidence: 97%
“…It is only recently that, in collaboration with the Cazin group,w ef ound that heating ad ioxane solution of iminium chloride 70 and Cu 2 O at 100 8 8Cf or 24 ha llowed for the preparation of (CAAC)-CuCl complexes (Scheme 21). [139] Soon after, we showed that these copper complexes can efficiently transfer the CAAC ligand to other transition metals,s uch as Pd, Au,a nd Ir. [140] Waldmann et al showed that av ariety of chiral (CAA-C)AuCl complexes 72 are accessible through a( Me 2 S)AuCl triggered cyclization-rearrangement of 1,7-enyne substrates 71 (Scheme 22).…”
Section: Coordination Chemistry Of Caacsmentioning
confidence: 99%
“…However, this reaction can take place in the presence of copper catalysts , . To enhance the rate of the CuAAC reaction, we tested CuCl and ( a NHC)CuCl, a complex bearing an abnormal N‐heterocyclic carbene ligand, as catalysts (Table ). We also tested 1,2‐dichloroethane (1,2‐DCE), a solvent with a higher boiling point than CH 2 Cl 2 , so that the reaction temperature could be increased and the reaction time decreased.…”
Section: Resultsmentioning
confidence: 99%